Early Life Stress, FKBP5 Polymorphisms, and Quantitative Glycemic Traits. Issue 5 (June 2017) - Suarez, Anna; Lahti, Jari; Kajantie, Eero; Eriksson, Johan G.; Räikkönen, Katri
ABSTRACT: Objective: Early life stress (ELS) has been shown to influence health later in life. Functioning of the hypothalamic-pituitary-adrenal axis, regulated partly by FKBP5 gene, may moderate these effects. We examined whether FKBP5 single-nucleotide polymorphisms (SNPs) interact with ELS on Type 2 diabetes, cardiovascular disease, and quantitative glycemic traits. Methods: A total of 1728 Helsinki Birth Cohort Study participants born from 1934 to 1944 were genotyped for FKBP5 SNPs (rs1360780, rs9394309, rs9470080) and were administered a 2-hour (75 g) oral glucose tolerance test and a questionnaire on physician-diagnosed and medication use for chronic diseases at a mean age of 61.5 years. Of the participants, 273 had been exposed to ELS, operationalized as separation from their parents, at a mean age of 4.7 years due to evacuations during World War II. Results: ELS interacted with FKBP5 SNPs in the analyses of fasting (rs1360780, p = .015), 30-minute (rs1360780, p = .031; rs9394309, p = .041) and incremental insulin (rs1360780, p = .032; rs9394309, p = .028; rs9470080, p = .043), insulin area under the curve (rs1360780, p = .044), and impaired fasting glucose (rs9470080, p = .049); among carriers of at least one copy of minor allele, but not among major allele homozygotes, insulin values were higher, as were the odds for impaired fasting glucose if they had been separated compared with if they had not. Corresponding associations were found with a haplotype formed by minor alleles in all three SNPs for fasting, 30-minute, and incremental insulin ( p < .05). Conclusions: FKBP5 polymorphisms in combination with ELS exposure predict higher insulin and glucose values in midlife. Our findings support the role for hypothalamic-pituitary-adrenal axis dysregulation in health-related metabolic outcomes. Abstract : Supplemental digital content is available in the text.